Beneath the Skin: The Relationship Between Psychological Distress and the Immune System in Patients with Psoriasis - Mahmoud Elsayed; Cody J. Connor (European Medical Journal, 2018)
Psoriasis is a chronic autoimmune skin disease with significant physical and psychiatric comorbidities. Research into psoriasis-associated depression has revealed several possible pathways linking the two very different diseases. Questions of causality arise when exploring the complex relationship of psoriasis and mood disorders, and studies have revealed that inflammation may serve as the common denominator linking psoriasis and depression. Conversely, many investigators have reported that psoriasis severity may fluctuate with perceived psychological distress, suggesting that psychological factors, rather than inflammation, may be the driving force behind disease exacerbation in these cases. The truth is likely a combination of both schools of thought: a bidirectional relationship between cutaneous and psychological disease manifestations with an overlapping biological mechanism associated with inflammation. Evidence has revealed multiple pathways by which this relationship can be explained, including hypothalamic-pituitary-adrenal axis hyperactivity, glucocorticoid receptor desensitisation, sympathetic nervous system activation, and altered expression of various chemical signals in the central nervous system. This review summarises the existing evidence and seeks to elucidate how the physiologic disturbances in psoriasis may contribute to both the cutaneous disease manifestations and associated psychological comorbidities. Evidence suggests that treating the psychiatric comorbidities of psoriasis can significantly improve cutaneous disease severity and treating the underlying inflammation could have profound effects on psychological health and quality of life. Therefore, conceptualising psoriasis as more than a purely dermatologic disease is useful in formulating a comprehensive treatment plan; furthermore, addressing both the cutaneous and psychological facets of this disease could prove profoundly beneficial for decreasing the associated negative impacts on patient quality of life.